Proposal for land use planning in the San Jerónimo de Surco-Huarochirí-Department of Lima sector - Buendía Ríos, Hildebrando (2001)
In the present investigation, they applied a methodology based on a territorial model and the use of management categories, in order to obtain and select alternatives aimed at the territorial organization of the San Jerónimo de Surco district, located in the province of Huarochirí, in the Lima department.